"Prices, taxes and subsidies in Pakistan agriculture 1960-1976" (Washington, 1980)
This paper is one of a member of companion papers which report on the results of a research project-- country case studies of Administered Agricultural Prices, Taxes and Subsidies, RPO 671-42 which commenced in the second half of 1976. The research , which included some desk studies besides the eight country case studies (Argentina, Egypt, Kenya, Mexico, Pakistan, Portugal, Thailand and Yogoslavia), was oriented towards eventually providing operational guidelines for country economic, agricultural sector and project planning work. Two of the country case studies involved the use of formal agricultural sector models (Mexico and Portugal), while the other six involved the use of a number of informal methodologies.
Keywords: Agricultural Price Support